Capital Market Integration In Some Asean Countries Revisited - Robiyanto, Robiyanto (Jurnal Manajemen, 2018)
Financial market integration in Southern Asia especially in ASEAN main member countries still attractive to scrunitized. Most of these countries were devastated during severe regional financial crisis in 1997 but global financial crisis in 2008 have different impact toward these countries. The finding shows that comovement were exist among Indonesia, Malaysia, Singapore and Thailand’s capital market during January 1997 to December 2013 period. Comovement still exist during post Asian financial Crisis 1997 and post global financial crisis 2008 period. This study conclude also that degree of integration between some ASEAN capital markets have fading out after global financial crisis in 2008. Hence, investor could formulate a portfolio which consist of stocks across ASEAN capital markets.